PENERAPAN TEKNIK TAILORING PADA BOLA DUNIA TAILOR DI PONDOK KOTA PADANG - Fitri, Corry Paratami; Zahri, Wildati; Yasnidawati, Yasnidawati (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2014)
This research was motivated by the good tailoring techniques are applied to the Bola Dunia Tailor in Pondok City Padang which includes models , materials , patterns and sewing techniques , resulting in a very good quality clothing . This study aims to determine the application of tailoring techniques to Bola Dunia tailor in Pondok CityPadang which includes the application of models , materials , patterns and sewing techniques . The method used is a qualitative case study method . This research was conducted in the city of Padang , data collection by observation , interviews , and documentation . Data analysis techniques are used , namely data reduction , data presentation and making conclusions . To obtain valid data in a way an extension of the observations , increase persistence , triangulation and auditing . The results of this study revealed that : 1 ) Model fashion tailoring techniques that made ​​Suit ( Suits ), which is also called the Jas . 2 ) The main material used is woll fibrous materials and semi- woll , auxiliary materials ( coatings ) coatings are used first ( Underlining ) consisting of cufner thick and thin , reinforcement material ( Interfacing ) consisting of Vukuda , cufner suits and velvet collar , and the last furing ( Lining ) sateen , complementary materials used are shoulder cushion ( padding ) , and the buttons are large and small . 3 ) The pattern used is a pattern that is constructed directly above the material . 4 ) sewing techniques sewing techniques used are in accordance with the sequence of work steps , such as installing a coating material ( fusing ) , bringing together the parts of suits , and the final settlement is done by using machine tools and manuals . Kata Kunci: Penerapan, Teknik, Tailoring